CRITICAL ORIENTATION IN BRIDGING MATHEMATICAL AND FOOD SECURITY LITERACY THROUGH PROBLEM-BASED STEAM-H - Fatimah, Ai Tusi; Isyanto, Agus Yuniawan; Erlin, Euis; Andriana, Bibin Bintang (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The increasing complexity of food security challenges requires vocational education to equip students with the ability to integrate mathematical reasoning and sustainability-oriented decision-making. However, previous studies have generally examined Mathematical Literacy and Food Security Literacy as separate competencies, resulting in a limited understanding of how these literacies interact within vocational learning contexts. This study aimed to investigate the effectiveness of Problem-Based Instruction integrated with the STEAM-H (Science, Technology, Engineering, Agriculture, Mathematics, and Health) framework in enhancing vocational students’ Mathematical Literacy, Food Security Literacy, and Critical Orientation. A convergent mixed-methods design was employed involving 24 eleventh-grade agribusiness vocational students. Quantitative data were collected through pretest–posttest holistic evaluation tests, while qualitative data were obtained concurrently through classroom observations and semi-structured interviews. The results revealed significant improvements in Mathematical Literacy and Food Security Literacy, accompanied by qualitative evidence indicating a shift from procedural computation toward evidence-based and sustainability-oriented decision-making. Three dimensions of Critical Orientation emerged from the qualitative findings, namely Cognitive Transition, Critical Disposition, and Comprehensive Critical Synthesis. The novelty of this study lies in conceptualizing Critical Orientation as a bridging construct connecting Mathematical Literacy and Food Security Literacy within a Problem-Based STEAM-H learning environment. These findings contribute to interdisciplinary literacy theory and provide practical implications for designing vocational curricula that promote higher-order thinking, sustainability awareness, and workforce readiness.